2012
DOI: 10.1038/jid.2011.378
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Cytokine Responses at the HLA-C Locus: Implications for Psoriasis

Abstract: Psoriasis is an inflammatory skin disorder that is inherited as a complex trait. Genetic studies have repeatedly highlighted HLA-C as the major determinant for psoriasis susceptibility, with the Cw*0602 allele conferring significant disease risk in a wide-range of populations. Despite the potential importance of HLA-C variation in psoriasis, either via an effect on peptide presentation or immuno-inhibitory activity, allele-specific expression patterns have not been investigated. Here, we used reporter assays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
3
21
0
2
Order By: Relevance
“…After stimulation with various cytokines, HLA-C expression was shown to be highly inducible in keratinocytes by a mix of the Th1-cytokine IFN-γ and the pro-inflammatory cytokines IL-1α and TNF-α (hereafter referred to as Th1-cytokine mix). The induction was largely dependent on IFN-γ (Figure 1a), which is in accordance with previously reported data (Hundhausen et al, 2012). In addition, we also analyzed HLA-C*06:02 mRNA presented herein may be required for to upregulate HLA-C*06:02 expression in keratinocytes.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…After stimulation with various cytokines, HLA-C expression was shown to be highly inducible in keratinocytes by a mix of the Th1-cytokine IFN-γ and the pro-inflammatory cytokines IL-1α and TNF-α (hereafter referred to as Th1-cytokine mix). The induction was largely dependent on IFN-γ (Figure 1a), which is in accordance with previously reported data (Hundhausen et al, 2012). In addition, we also analyzed HLA-C*06:02 mRNA presented herein may be required for to upregulate HLA-C*06:02 expression in keratinocytes.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 91%
“…PSORS1 lies within the class I region of the MHC, and there is consensus that HLA-C is the most likely PSORS1 gene (105). The exact functional implications of alleles at this locus are not yet fully known, although there appear to be allele-specific differences in HLA-C expression and regulation by cytokines in psoriasis (107). Given our understanding that HLA class I molecules are important for antigen presentation to CD8 + T cells, this locus links the genetics of psoriasis with the immunological basis of the disease.…”
Section: Genetic Background Of Psoriasis and Its Relationship To Immumentioning
confidence: 99%
“…Nevertheless, sequence and haplotype analysis (Nair et al 2006), genome-wide association studies (GWASs) Strange et al 2010;Tsoi et al 2012), and analysis of high-density single-nucleotide polymorphism (SNP) data, further refining PSORS1 interval to a 179-kb region encompassing HLA-C (Clop et al 2013), have consistently indicated HLA-C as the most likely PSORS1 gene. SNPs within the minimal promoter region of HLA-C result in differential expression of various alleles, including HLA-Cw à 0602 (Hundhausen et al 2012). Moreover, regulatory variants in the putative HLA-C enhancer element are also likely to contribute to psoriasis susceptibility by affecting HLA-C expression (Clop et al 2013).…”
Section: Psors1mentioning
confidence: 99%